Intervening Effect of Hybrid Method in Enhancing Teachers’ Engagement and Satisfaction - Operio, Jennifer (RSF Conference Series: Business, Management and Social Sciences, 2025)
This research examined the intervening effect of technology expressed as the hybrid method or approach in enhancing teachers’ engagement and satisfaction in imparting knowledge to the Senior High School level of Holy Angel University (HAU). It particularly sought answers to the following: (1) Is the hybrid learning approach being utilized in teaching subjects to HAU’s Accountancy, Business and Management (ABM) strand students? (2) What are the barriers to using hybrid learning techniques in teaching these HAU’s ABM strand students? (3) How may the level of effectiveness be described in using a hybrid learning technique? (4) What are the advantages of utilizing hybrid approach as a teaching method? (5) What is the most/least effective aspect of hybrid learning as a teaching method? Descriptive-quantitative research was utilized. Fifty senior high school teachers teaching ABM strand students are targeted. However, only 35 filled-out survey forms were turned in. The utilization or possible integration of technology in teaching subjects to students at the Senior High School level was identified. Ethical considerations were employed in conducting this research: respect for anonymity and confidentiality of the information collected; respect for privacy – respondents were given ample time in answering the survey questionnaire; they were protected in such a way that they did not feel intimated, the proponent let another person conduct the survey and was not directly involved with the distribution and collection of the survey instrument. Validation of the instrument was also done through a group of people with similar characteristics to the respondents of the study. An expert in research and statistics with so many years of experience doing researches were also consulted. Results show that though teachers utilized the hybrid approach, a small percentage of them still fully utilized the traditional approach in providing information to their learners. Technology and advancements have their own pros and cons. Research could be made to have equal. Footing for all types of students on the utilization and application of technology to the current curriculum of the ABM strands without letting the more emphatic way of addressing their needs. As a recommendation, the researcher proposes further research that could be triangulated, which will involve students and school administrators to further validate the mediating effect of hybrid learning on students’ engagement.